PERBANDINGAN RENDEMEN EKSTRAKSI KECOMBRANG (Etlingera elatior) MENGGUNAKAN METODE MASERASI DAN SOKLETASI - Nurmalasari, Enny; Miftahurrahmah, Miftahurrahmah; Nurillahi, Resi; Cahyani, Luthfi Nazwa Andya (Politeknik ATI Padang, 2023)
Torch ginger (Etlingera elatior) contains secondary metabolites that have antibacterial potential. The production of torch ginger extract in Indonesia is still limited. However, market demand increase because pharmaceutical industry is starting to use the torch ginger extract. Furthermore, the growing utilization of torch ginger will enhance the economy of torch ginger farmers. This study aims to compare the extraction efficiency of maceration and soxhletation methods in obtaining bioactive compounds from torch ginger using ethanol, methanol and n-hexane as solvents. The results showed that in the maceration method, ethanol solvent produced the highest yield of 15%, methanol 7% and n-hexane 3%. In soxhletation method, ethanol and methanol solvents produced yields of 15% and 13% respectively, higher than n-hexane only 1%. Overall, soxhletation method with ethanol solvent was the best condition for torch ginger extraction. GC-MS characterization showed the presence of bioactive compounds such as 2-Chloropropionic acid, Boric acid trimethyl ester, Silane dimethoxymethyl and Octadecanoic acid methyl ester which contribute to the antibacterial activity in torch ginger essential oil.